Self-Confidence Conceptual Model Development in Volleyball Learning Courses - Yuni Astuti; Zulbahri Zulbahri; Haripah Lawanis; Erianti Erianti; Damrah Damrah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The research was motivated by the problem of students in the Physical Education, Health and Recreation Study Program not exhibiting optimal self-confidence, particularly the confidence to speak in front of the class during lecture activities. Self-confidence is an aspect of the human psyche that must be nurtured and developed. Self-confidence denotes the ability to do something confidently and without fear of failure. Confidence is also part of the subconscious and is unaffected by emotions and feelings. Therefore, it requires a method that can be accomplished by controlling emotions, feelings, and imagery. The volleyball learning course necessitates good psychological conditions for students to be confident when practicing in small groups and later when conducting teaching practice at school. In this course students are equipped with basic techniques in playing volleyball and how to construct volleyball learning tools, then students are able to practice teaching in small groups. This study employs a qualitative approach with a classroom action research design that follows the lecture schedule. The research procedure is divided into two cycles, with each cycle consisting of five stages: planning, action, observation, evaluation, and reflection. This research was conducted in two cycles and the time required was 5 weeks for each cycle so that the total time required was 10 weeks with two cycles. The research subjects were 50 students who took the volleyball learning course. Data collection methods include observations and interviews. The results of the study show that in an effort to increase student self-confidence, the strategy chosen is role-playing which provides broad opportunities for students to explore themselves in order to be able to demonstrate their quality in front of other friends to become teachers in the teaching practice of the material chosen by each student. In this study, the role-playing technique was seen to be successful in increasing the self-confidence of the students.